Production of immune-modulatory nonclassical molecules HLA-G and HLA-E by tumor infiltrating ameboid microglia/macrophages in glioblastomas: a role in innate immunity? - Křen, Leoš; Múčková, Katarína; Lžičařová, Eva; Sova, Marek; Vybíhal, Václav; Svoboda, Tomáš; Fadrus, Pavel; Smrčka, Martin; Slabý, Ondřej; Lakomý, Radek; Vaňhara, Petr; Křenová, Zdenka; et al. (Journal of neuroimmunology, 2010)
The possible role of immune-modulatory nonclassical molecules HLA-G and HLA-E in an anti-tumoral response and development of glioblastoma is not well characterized. In this study, we evaluated an expression of HLA-G and HLA-E by activated tumor infiltrating microglia/macrophages. We found production of HLA-G and HLA-E by tumor infiltrating activated microglia/macrophages in a majority of glioblastomas. We speculate that the expression of these molecules by activated microglia/CNS macrophages plays a role in the anti-tumoral immunity in the development of glioblastoma. Mechanisms of microglia-glioblastoma cell interactions with respect to the expression of these molecules deserves further study.
Keywords: přirozená imunita; Cell Movement; glioblastom; HLA-G Antigens; mozek; Histocompatibility Antigens Class I; Humans; Brain; pohyb buněk; makrofágy; Microglia; Gliosis; Glioblastoma; HLA Antigens; MHC antigeny I. třídy; mikroglie; Immunomodulation; Brain Neoplasms; Immunity, Innate; Macrophages; nádory mozku; HLA-G antigeny; lidé; imunomodulace; Cell Communication; mezibuněčná komunikace; glióza; HLA antigeny